Validation of the name Homalomena brachygyna (Collantes et al. in Phytotaxa 664 (1): 60) - Hein, Khant Zaw; Collantes, John Paul (Phytotaxa, 2025)
The name Homalomena brachygyna J.Collantes, K.Z.Hein & R.Bustam. was proposed for a new species of Homalomena Schott (1832: 20) from Palawan, Philippines, and published in Phytotaxa on 3 September 2024 (Collantes et al. 2024). However, the name is invalid under Article 40.5 of the International Code of Nomenclature for algae, fungi, and plants (Turland et al. 2025), as the protologue failed to specify a single institution where the holotype is conserved—a requirement for valid publication of names published after 1 January 1990. Instead, two institutions were cited: PNH for the sheet and CAHUP for the spirit material (Collantes et al. 2024). As all other requirements of the Madrid Code were fulfilled, Homalomena brachygyna is validated below by unambiguously designating the holotype, using the effective English diagnosis and description provided in Collantes et al. (2024).